The Effect of Using Xtra - Man Apparatus on Developing Motor Response Speed In Advance Basketball Players - Hareth Mobesher Mohameed; Muhannad abdulsattar Alaany (College of Physical Education and Sport Sciences, 2021)
The research aimed at using Xtra - Man apparatus on advanced basketball players, designing a test for motor response speed, preparing Xtra - man apparatus exercises for advanced basketball players, and identifying the effect of these exercises using Xrat - Man apparatus on developing motor response speed in advance basketball players.  The researchers used the experimental method on (12) advanced basketball players from Al Adhamia club. After applying for the training program the data was collected and treated using proper statistical operations to conclude that special exercises using Xtra - Man have a significant effect on the development of motor response speed in advanced basketball players.